Predicting Traffic Accidents In Lattakia Governorate Using ARIMA Models (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research aims to study the reality of traffic accidents in Lattakia Governorate, including deaths and injuries, and the resulting difficulties, due to the factors causing their occurrence.And study the concept of ARIMA models and the steps to apply these models. In addition to predicting the number of traffic accidents in Lattakia Governorate for the coming period from 2021_2025, perhaps the most famous models used in the prediction process is the integrated Auto regression model with the moving average ARIMA, which was used in this research to predict traffic accidents in Lattakia Governorate, and we have reached this research after a test Stability of the time chain within 60 months from 2016 to 2020 and analyzing it and choosing the appropriate ARIMA model to the following results: The model that makes the series stable when taking the difference from the second rank  is Arima (1.2.1) , and has also been reached as it is possible to build a model to predict the number of traffic accidents in Lattakia depending on models ARIMA The data predicted has been obtained regarding the number of traffic accidents until the end of 2025 .